Occupational Contact Dermatitis in Mechanics and Repairers Referred for Patch Testing: Retrospective Analysis From the North American Contact Dermatitis Group 1998–2014. Issue 1 (January 2017) - Warshaw, Erin M.; Hagen, Solveig L.; Sasseville, Denis; Maibach, Howard I.; DeKoven, Joel G.; Belsito, Donald V.; Fowler, Joseph F.; Zug, Kathryn A.; Taylor, James S.; Mathias, C.G. Toby; Fransway, Anthony F.; DeLeo, Vincent A.; et al.
Abstract : Background: Contact dermatoses are common in mechanic and repair occupations. Objectives: This study aimed to (1) estimate the prevalence of occupationally related contact dermatitis among mechanics/repairers patch tested from 1998 to 2014 by the North American Contact Dermatitis Group, (2) characterize responsible allergens and irritants, and their sources, and (3) compare results among 3 occupational subgroups (mechanics, electrical/electronic, and other). Methods: A cross-sectional analysis of patients patch tested by the North American Contact Dermatitis Group between 1998 and 2014. Results: Of 38, 784 patients patch tested, 691 (1.8%) were mechanics/repairers. Male sex (93.5%) and hand involvement (59.5%) were common overall. Occupationally related skin disease was more prevalent among vehicle and mobile equipment mechanics/repairers (52.7%) and other mechanics/repairers (41.4%) than electrical/electronic equipment mechanics/repairers (21.3%). Overall, carba mix, thiuram mix, and methylchloroisothiazolone/methylisothiazolone were the most common occupation-related clinically relevant allergens. Gloves, automotive vehicles, solvents, oils, lubricants, and fuels were the most common sources of responsible allergens. Conclusions: Common occupationally related allergens included rubber accelerators and the preservative methylchloroisothiazolone/methylisothiazolone.